The Effect of Amount of Tumeric Powder Quality of Tofu at Room Temperature Storage - Candra Ginting; Sentosa Ginting; Ismed Suhaidi (Jurnal Rekayasa Pangan dan Pertanian, 2014)
This study was performed to determine the effect of the addition of turmeric powder on tofu quality at room temperature storage. Method of this study was completely randomized design with two factors i.e. the amount of turmeric powder (K) : (0 %), (2 %), (4 %), and (6 %) and storage time (L) : (0 days), (2 days), (4 days), and (6 days). The analyzed parameters were total microorganism, tofu acidity, immersion water acidity, moisture content, ash content, protein content, sensory test (color, aroma, flavor, and texture).The amount of turmeric powder had highly significant effect on total microorganism, tofu acidity, immersion water acidity, ash content, and sensory test ( color, aroma, flavor, and texture). Storage time (L) had highly significant effect on total microorganism, tofu acidity, immersion water acidity, water content, protein content, and sensory test (color, aroma, taste, and texture). The interaction of turmeric powder and storage time had highly significant effect on total microorganism and color. The best composition which gave the best effect on tofu was 2 % of turmeric powder and 4 days storage. Keywords: storage,  time, tofu, turmeric powder